Evaluation of a dynamic navigation system for training students in dental implant placement. Issue 2 (10th September 2020) - Zhan, Yalin; Wang, Miaozhen; Cheng, Xueyuan; Li, Yi; Shi, Xiaorui; Liu, Feng
Abstract: Objective: Computer‐guided simulation systems may offer a novel training approach in many surgical fields. This study aimed to compare dental students' learning progress in dental implants placement between a dynamic navigation system and a traditional training method using a simulation model. Methods: Senior dental students with no implant placement experience were randomly assigned to implant placement training using a dynamic navigation system or a traditional freehand protocol. After training, 3‐dimensional (3D) deviation at implant platform, 3D deviation at implant apex, and deviation of implant axis between the planned and placed implant positions were measured using superimposed cone beam computed tomography scans. Results: Six students were trained in this study. Students showed significantly greater improvement in implant placement after training using the dynamic navigation system than after using the traditional freehand protocol. Overall deviation of implant axis ( P < 0.001) and 3D apex deviation ( P = 0.014) improved with training using the dynamic navigation system, but differences in 3D platform deviation ( P = 0.513) were not statistically significant. Conclusions: A dynamic navigation system may be a useful teaching tool in the early development of clinical skills in implant placement for the novice practitioners. Novice practitioners exhibited significant improvement in angulation deviation across implant placement attempts with dynamic navigation system training.